Fetal And Maternal Outcomes In Pregnant Women With Hypothyroidism: An Observational Study In A Tertiary Care Hospital (East West Medical College Journal, 2026)
Hypothyroidism is  common  during pregnancy. Maternal and fetal complications are higher in women with hypothyroidism compared to euthyroid women. So optimal maternal thyroid function during pregnancy is important for both the mother and the fetus. This observational study  aimed to study the foetomaternal outcome among pregnant hypothyroid women. It  was carried out in  the department of Obstetrics and Gynaecology   in  Ad-din Women’s   Medical College Hospital, Maghbazar, Dhaka from Ist July  2024 to 30 th  June 2025. The  study included 108  hypothyroid  pregnant  women to observe fetal and maternal effects of hypothyroidism. Patients were collected as per inclusion and exclusion criteria after informed written consent. Maternal complications  like preeclampsia, postpartum haemorrhage, gestational hypertension, anaemia and postpartum depression were common in hypothyroid pregnant  women .on the other hand, adverse fetal  outcome, such as preterm birth, abortion, IUGR, respiratory distress and still birth  were  common  in hypothyroid  cases. To prevent  these adverse fetomaternal  outcome  routine maternal thyroid function testing should be done as early as possible.EWMCJ Vol. 14, No. 2, July 2026: 183-186